Environmental and Climate Impacts on Physiological Aging: Comprehensive Pathways to Enhanced Age-related Resilience - Chengmeng Zhang; Shangjun Liu; Chen, Gong (Aging and disease, 2025)
This perspective article highlights the pressing necessity to focus on heterogeneity in organ-specific aging, emphasizing the influence of environmental and climate changes, as well as social interactions, on the aging process of individual organs. It explores innovative and integrative strategies tailored to the unique aging mechanisms of different organs, aiming to preserve their biological clocks. By emphasizing the importance of addressing organ-specific vulnerabilities, the article calls for transcending traditional pharmacological treatments and organ transplants. It proposes a comprehensive approach that combines environmental management, social support systems, and advanced technological interventions to improve the well-being and longevity of aging populations.